Development of world class ski performance: Similarities and differences in pathways to expertise for freeskiers and cross-country skiers - Aalberg, Martine; Roaas, Truls Valland; Aune, Morten Andreas; Aune, Tore Kristian (Current Issues in Sport Science (CISS), 2024)
The overall purpose of the present study was to investigate similarities and differences in pathways to expertise for freeskiers and cross-country skiers. Specifically, 1) Entrance to the main sport, 2) Amount of training hours and organization of training, and 3) Variability in activities and content in training. Sampling athletes had to be on the highest level in their sport by competing in, e.g., the World Cup, World Championship, Olympic games, freeride World Tour. In total, 18 world-class skiers participated in the study. Eight freeskiers (age range 19-37) and ten cross-country skiers (age range 22-32 years). They answered a digital questionnaire designed to collect retrospective data describing their pathways to expertise. The first section elicits biographical information, age for entering sport and practice. The second section focused on sport-specific training, accumulated hours of training, and the distribution of organized versus self-organized training. The third section recalled the variability of activities they participated in and how they perceived the relevance of the content of different types of training for their sport-specific development. The results showed similarities in athletes’ entrance to the main sport, specialization age and total amount of training. At the same time, differences were observed in their training history regarding the organization of training. In contrast to cross-country skiers, freeskiers seem to be more self-organized and more involved in additional activities besides their main sport. Interestingly, the two groups of world-class athletes representing sports with distinctive demands share several common variables in their paths to expertise, amplified by perceived specificity. Practitioners and academics should substantiate patience in expertise development, driven by a multi-disciplinary understanding of distinct and individual characteristics or conditions that may be beneficial in fulfilling varied future demands. Hence, research should explore the rationale behind and potential learning effects between sports and training content.